Working in cases: British psychiatric social workers and a history of psychoanalysis from the middle, c.1930–60. (July 2021) - Broad, Juliana
Histories of psychoanalysis largely respect the boundaries drawn by the psychoanalytic profession, suggesting that the development of psychoanalytic theories and techniques has been the exclusive remit of professionally trained analysts. In this article, I offer an historical example that poses a challenge to this orthodoxy. Based on extensive archival material, I show how British psychiatric social workers, a little-studied group of specialist mental hygiene workers, advanced key organisational, observational, and theoretical insights that shaped mid-century British psychoanalysis. In their daily work compiling patient histories, conducting home visits, and interviewing the parents of 'maladjusted' children, psychiatric social workers were uniquely positioned to expose the importance of family relationships in the development of childhood neuroses. As this article details, their analytic attention to these dynamics not only influenced, but fundamentally constituted the innovative research on maternal-child relationships and family therapy pioneered by eminent psychoanalyst John Bowlby. In addition, psychiatric social workers produced and published independent psychoanalytic research, and fiercely debated the limitations of analytic concepts such as transference. In presenting the relationship between British psychiatric social work and psychoanalysis, this article suggests a new way of telling the history of both.